Líneas de investigación y recursos bibliográficos sobre inmigración en Madrid - Sassano, Silvana; Meike Willems, Carmen; Tello García, Jaime (Anales de Geografía de la Universidad Complutense, 2002)
There has been a high number of publications, references, articles and books on Immigration during the last fifteen years. It’s the importance of this matter, specially in the urban region of Madrid, that promoted it to be an interesting issue to be studied by many sciences: geography and sociology. This article is showing the most important documents on immigration in Madrid, since 1990.